Applications Based on Expert Systems For Early Diagnosing Anemia in Pregnant Women - Meizar Abdul; Nur Hayati; Utami Utami (Sean Institute, 2022)
Anemia in pregnant women is commonly called iron deficiency anemia with hemoglobin levels in red blood cells 10.0 grams/100 milliliters (10 grams/deciliter). This type of anemia is prone to be experienced by pregnant women because pregnant women must require very high oxygen levels. This type of anemia is not so dangerous but can be dangerous if there are congenital abnormalities of the body. Therefore, the authors feel it is important to identify this type of anemia early because there is a dangerous potential. The author makes an application based on an expert system that early diagnoses a pregnant woman with iron deficiency anemia or not. The method used is Bayes' theorem. The results obtained are efficiency and speed in early diagnosis of anemia in pregnant women used in hospitals. Coal Inalum. With a situation where the hospital only has one doctor serving many pregnant women patients. With the application of an expert system for early diagnosis of anemia in pregnant women, it can help users (doctors) in knowing the early symptoms of whether a pregnant woman has iron deficiency anemia or not.